Efisiensi Anggaran dan Dampaknya terhadap praktik Good Governance di Kementerian Dalam Negeri dalam Era Reformasi Birokrasi - Darmawan, Muhamad; Athalla, Muhammad Rifqy Addin; Hutasoit, Onma Bryan Yehezkiel; Cahyadi, Raihan Dwi; Lukman, Firman (Journal of Social Contemplativa, 2025)
This research aims to analyze the relationship between bureaucratic reform, good governance principles, and budget efficiency policies in the context of the Ministry of Home Affairs (MoHA) of the Republic of Indonesia. Using a descriptive qualitative approach and public policy analysis, this research outlines how the implementation of Thematic Bureaucratic Reform contributes to improving the performance of government institutions. The findings show that the Ministry of Home Affairs has successfully implemented reforms, especially in the aspects of poverty alleviation and inflation control, which are aligned with good governance indicators. However, challenges such as political intervention, bureaucratic resistance, and a potential legitimacy crisis due to budget efficiency inequality remain significant obstacles. Budget efficiency, while supporting fiscal rationalization and service innovation, must be balanced with the principles of social justice and public accountability. In conclusion, the synergy between bureaucratic reform and budget efficiency can only be optimally realized if supported by participatory, responsive and results-oriented governance.